Cribriform neuroepithelial tumor: molecular characterization of a SMARCB1-deficient non-rhabdoid tumor with favorable long-term outcome - Johann, Pascal-David; Hovestadt, Volker; Korshunov, Andrey; Capper, David; Jones, David T. W.; Pfister, Stefan; Kool, Marcel (Brain pathology, 2017)
Rhabdoid phenotype and loss of SMARCB1 expression in a brain tumor are characteristic features of atypical teratoid/rhabdoid tumors (ATRT). Rare non-rhabdoid brain tumors showing cribriform growth pattern and SMARCB1 loss have been designated cribriform neuroepithelial tumor (CRINET). Small case series suggest that CRINETs may have a relatively favorable prognosis. However, the long-term outcome is unclear and it remains uncertain whether CRINET represents a distinct entity or a variant of ATRT. Therefore, 10 CRINETs were clinically and molecularly characterized and compared with 10 ATRTs of each of three recently described molecular subgroups (i.e. ATRT-TYR, ATRT-SHH and ATRT-MYC) using Illumina Infinium HumanMethylation450 arrays, FISH, MLPA, and sequencing. Furthermore, outcome was compared to a larger cohort of 27 children with ATRT-TYR. Median age of the 6 boys and 4 girls harboring a CRINET was 20 months. On histopathological examination, all CRINETs demonstrated a cribriform growth pattern and distinct tyrosinase staining. On unsupervised cluster analysis of methylation data, all CRINETs examined exclusively clustered within the ATRT-TYR molecular subgroup. As ATRT-TYR, CRINETs mainly showed large heterozygous 22q deletions (9/10) and SMARCB1 mutations of the other allele. In two patients, SMARCB1 mutations were also present in the germline. Estimated mean overall survival in patients with CRINETs was 125 months (95% confidence interval 100-151 months) as compared to only 53 (33-74) months in patients with ATRTs of the ATRT-TYR subgroup (Log-Rank P < 0.05). In conclusion, CRINET represents a SMARCB1-deficient non-rhabdoid tumor, which shares molecular similarities with the ATRT-TYR subgroup but has distinct histopathological features and favorable long-term outcome.
First published: 06 July 2016
Gesehen am 20.11.2018